The Irish Football Player Pathway: Examining Stakeholder Coherence Throughout and Across the Player Development System - Liam Sweeney; Áine MacNamara; Dan Horan (Frontiers Media S.A., 2022)
Maximizing the efficiency of the player development system is a strategic priority for any professional football club or association. However, the successful development of a young footballer is largely dependent upon the roles and relationships of the different stakeholders invested in the developmental process. This study examined the level of horizontal (i.e., extent to which stakeholders across a pathway stage work with players in an agreed fashion to optimize their experience) and vertical (i.e., extent to which multiple stages of the pathway are coordinated and build chronologically from previous involvement toward long-term needs) stakeholder coherence throughout the Irish football player pathway following a restructuring of development policies and the implementation of a nationwide academy system between 2016 and 2020 under the Football Association of Ireland's (FAI) Player Development Plan. As a second aim, we explored each of the key stakeholders' alignment to academic talent development principles in order to provide practical recommendations for future player and coach development policies. Accordingly, a series of interviews were conducted with 31 key stakeholders currently engaged in the player pathway. These key stakeholders consisted of parents, coaches and members of the FAI as the National Governing Body for football in Ireland. Data were analyzed using Reflexive Thematic Analysis, with findings highlighting a lack of stakeholder coherence across the pathway, both vertically and horizontally. Stakeholders displayed inconsistency in their understanding of the purpose of the player pathway and its long-term strategic aims, as well as demonstrating poor and incohesive relationships with each of the different stakeholders. Moreover, talent development principles between the different stakeholders appeared well-understood overall, although the practical implementation of several of these principles in applied practice did not appear to exist. Results highlight the need for organizational intervention and structural change across the Irish player pathway to maximize long-term player development in the future. Practical implications for the FAI are discussed and recommendations are made to support optimal player development policies moving forward.